2015
DOI: 10.1615/intjmedmushrooms.v17.i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anticonvulsant, Antidepressant-, and Anxiolytic-like Effects of an Aqueous Extract from Cultured Mycelia of the Lingzhi or Reishi Medicinal Mushroom Ganoderma lucidum (Higher Basidiomycetes) in Mice

Abstract: Ganoderma lucidum is a well-known medicinal mushroom with a long history of use. This study was designed to assess the anticonvulsant potential of an aqueous extract from cultured G. lucidum mycelium in 3 acute seizure models: timed intravenous pentylenetetrazole infusion, maximal electroshock seizure threshold, and 6-Hz-induced psychomotor seizure tests in mice. Moreover, antidepressant-like and anxiolytic-like effects of G. lucidum were evaluated using the forced swim test and the elevated plus maze test in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…There are few reports describing anticonvulsant activity of polysaccharides isolated from Ganoderma species. 14,15 The anticonvulsant activity induced by GCPS-2 is similar to that reported by us with an oligosaccharide fraction from a Ganoderma lucidum strain collected in a Mexican forest. 16 These results suggest that GCPS-2 is a natural compound with potential anticonvulsant activity.…”
Section: Discussion/conclusionsupporting
confidence: 78%
“…There are few reports describing anticonvulsant activity of polysaccharides isolated from Ganoderma species. 14,15 The anticonvulsant activity induced by GCPS-2 is similar to that reported by us with an oligosaccharide fraction from a Ganoderma lucidum strain collected in a Mexican forest. 16 These results suggest that GCPS-2 is a natural compound with potential anticonvulsant activity.…”
Section: Discussion/conclusionsupporting
confidence: 78%
“…10 Preclinical research demonstrated a reduction in the duration of immobility in the forced swimming test in mice and rats orally treated with 100-400 mg/kg and 1 g/kg, respectively, of MAK. 10,11 Notably, these findings are similar to those after the administration of serotonergic (5-HT) antidepressants. 12 Of note, head-twitch responses that signal 5-HT2A receptor activation were reduced by MAK, suggesting the involvement of this receptor in MAK's antidepressant actions.…”
Section: Introductionsupporting
confidence: 67%
“…15 Importantly, preclinical research has also shown the absence of toxic, anxiolytic-like, or sedative effects in mice, after treatment with MAK, in doses up to 2500 mg/kg, for some parameters. 11 Also, clinical trials seem to support this safety profile of GL, or fractions (polysaccharides) of GL, as it is generally well tolerated after repeated administrations, for several months. 16,17 A patient with PD who just started using Ganoderma lucidum contacted the author.…”
Section: Introductionmentioning
confidence: 96%
“…The lyophilized G. lucidum mycelium, provided by BRASMICEL-SP was deposited on the Micoteca of the Laboratório de Bioprocessos de Cogumelos—DEALI (UNICENTRO, Guarapuava, Paraná, Brazil) and triturated, mixed with distilled water and homogenized in the vortex for five minutes. The resulting suspension was filtered and administered orally at a final volume of 0.1 ml for each 100 g of animal weight, equivalent to 100 mg/kg/day [ 25 ].…”
Section: Methodsmentioning
confidence: 99%